Report on gubernatorial votes (Document (Maine. Legislature. Senate) ;, 1838)
Senate version of 1838 Report of the Joint Select Committee regarding the election for governor and the appropriate victor as between Edward Kent and Gorham Parks and the remonstrances from various sources, particularly in regarding to the returns from Leeds, Fairfield, and Fayette.